Efektivitas Sistem Pengendalian Internal, Ketaatan Aturan Akuntansi, Implementasi Good corporate governance dan Fraud di Masa Pandemi Covid-19 pada PT. Sarindo Makmur Sejahter - Nelli Novyarni; Debi Arianti; Reni Harni (Jurnal EMT KITA, 2023)
This study aims to examine whether there is an influence on the effectiveness of the Internal Control Sistem, Compliance with Accounting Rules, and the Implementation of Good corporate governance on Fraud During the Covid-19 Pandemi.This research uses a type of causality research with a quantitative approach, which is measured using a multiple linear regression based method with SPSS version 24.00. the population of this study is PT. Sarindo Prosperous Prosperity. The sample was determined based on the purposive sampling method, with a total sample of 30 respondents. The data collected in this research is in the form of primary data. Data collection techniques using a questionnaire in the form of a questionnaire distributed to employees of PT. Sarindo Prosperous Prosperity. Hypothesis testing using t test and f test. The results of the study prove that (1) the Effectiveness of the Internal Control Sistem has an effect on Fraud during the Covid-19 Pandemi, (2) Compliance with Accounting Rules has an effect on Fraud during the Covid-19 Pandemi, (3) Implementation of Good corporate governance has an effect on Fraud in The Covid-19 Pandemi Period. (4) The effectiveness of the Internal Control Sistem, Compliance with Accounting Rules, and the Implementation of Good corporate governance have a simultaneous effect on Fraud in the Covid-19 Pandemi Period.